Wirtschafts- und sozialgeographische Wandlungen des Fremdenverkehrs in Zypern - Heinritz, Günter (ERDKUNDE, 1972)
The strong growth experienced by tourism in Cyprus in the course of the last five years has been accompanied by an incisive change in its structure. Up to the end of the British colonial period, tourism was largely limited to a few Greek mountain villages in the Troodos Mountains used as summer resorts by the British who lived on Cyprus or in the Near East. After independence had been achieved, the Cyprus Government took steps to expand tourism, a goal which has been achieved thanks to the enterprise and enthusiasm of a group of local entrepreneurs. The hotel capacity which, up till then, had been very modest was not only quantitatively increased but also qualitatively altered in favour of luxury hotels and was spatially relocated from the mountains to the coast, especially Famagusta. These changes on the supply side have been matched by changes in the composition of hotel guests, in which central and north Europeans with relatively strong purchasing power are especially important. While the summer resorts of the Troodos Mountains continue to lose importance, the mountains are gaining new functions as local recreation areas for the Cypriot populaion.